Developing Remo Asri Kusuma Dance as an Institutional Identity Through Early Childhood Education Students - Dhirgan Grudhowaringin; Gesang Bayu Pamungkas; Astrid Wangsagirindra Pudjastawa (Mahesa Research Center, 2026)
This research aims to develop a Remo Asri Kusuma dance tutorial video as an enrichment medium for Early Childhood Education (ECE) students in creating new choreographed dances that serve as institutional identities. The study employs the Research and Development (RD) method using the Borg and Gall model, simplified into five primary stages: (1) preliminary study and information gathering, (2) initial product draft development, (3) expert validation (content and media), (4) field testing (small and large groups), and (5) final product revision. Research instruments utilized Likert scale questionnaires to measure media feasibility. The results indicate that the tutorial video is categorized as